Estoques e fluxos de C e N em Sistemas agrícolas tradicional e agroflorestais no Semiárido brasileiro. - Sacramento, José Augusto Amorim Silva do (2012)
The objective was to assess the changes promoted in the stocks and flows of C and N from the soil by farming systems agroforestry (agrosilvipasture - AGP and silvipasture - SILV) and traditional (TR), compared to natural vegetation of Caatinga (VN), after 13 years, the experiment was installed on a typical Ortic Chromic Luvisol, the city of Sobral, Ceará. Soil samples were collected at depths 0-6, 6-12, 12-20, 20-40 and 40-60 cm, relief in four replicates per. Was determined by the total carbon carbon (TOC); total nitrogen (NT) and bulk density. The gas flow was measured using an analyzer in the field of O2, CO2, NO / NO x and SO 2 (UNIGAS Eurotron 3000). To this end, were used for still cameras based on galvanized steel and PVC cover installed in the field. The sampling was done in three replicates, considering the relief plan, convex and concave in each study situation. For each determination were performed triplicate, totaling nine chambers for relief. Soil samples were collected for determination of soil bulk density (Ds) and particle (Dp) and gravimetric moisture (Ug), which allowed the calculation of total porosity (Pt) and the pore space filled with water (EPPA). Among the agroforestry systems studied, the silvipasture, long-term, promoted greater reductions in C stocks and N, the system promoted agrossilvipastroil lower losses and represents a sustainable alternative to sequestration of soil C and N in the Brazilian semi-arid conditions. The traditional cropping system provided a reduction of 58.87 and 9.57 (Mg ha-1), which meant, a reduction of 6.5 and 1.06 (Mg ha-1), for those of TOC and TN, respectively. These results demonstrate the inadequacy of this system for the Brazilian semi-arid conditions. The concave topography (AGP) and flat (SILV) showed the highest values of TOC. For NT the concave shape (VN, AGP, and SILV) showed the highest values. Flows of C-CO2 varied with the time, AGP and SILV being similar to NV in the wet season, while in the dry season are higher. The TR has a different behavior, being higher during the wet season and similar to AGP and SILV in the dry. The flow behavior of NO present without a tendency similar to C-CO2: AGP and SILV presents similar to each other in the wet season, but smaller than VN. During the dry SILV and VN are larger than AGP. In TR NO was not detected in the two periods. The convex shape of relief TR system showed the highest values of C-CO2 fluxes in the wet season. In the dry season were found higher values of C-CO2 flows in AGP, SILV and RT, compared to NV flat terrain. Soil moisture was the variable most correlated with the fluxes of NO, what might be observed in systems SILV and AGP and VN convex reliefs.